(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
Available in forms of lexicographic materials in Uzbek language, Uzbek language and its explanatory dictionaries, dictionaries, articles, books prepared for readers and other types of information. This material is an important basis for learning the language, learning the rules of the language, the rules of speech and a deeper understanding of the Uzbek language. The analysis of these materials, on the other hand, helps to understand their available information and track the news in the Uzbek language.